Mengaplikasikan Ilmu Sejarah Melalui Gambar-Gambar Peradaban di SMPS Al-Wasliyah Desa Pasir Permit - Samin Lubis, Mara; Sepriani, Laila (PT. Alahyan Publisher Sukabumi, 2024)
This study was carried out to complete the KKN's tasks carried out in Batu Bara Regency, Limapuluh District, in Izin Pasir Village. This research method was carried out using a qualitative method which was carried out to understand a context regarding Applying Historical Knowledge Through Images of Civilization at AL-WASLIYAH SMPS, PASIR PERMIT VILLAGE using infocus delivered by class X students of AL-WASLIYAH SMPS by using several images. about civilizations such as the tombs in Barus, Bongol Temple, Maimun Palace, Al-Mashun Grand Mosque.